1990
DOI: 10.1002/smj.4250110502
|View full text |Cite
|
Sign up to set email alerts
|

Middle managers and strategy: Microdynamics of inclusion

Abstract: This paper examines the role of middle management in strategic processes in bureaucratic organizations. There is evidence of extensive dissatisfaction among middle managers, who often perceive that they are excluded from strategic processes. This exclusion is de‐energizing, inefficient, and in the end, expensive. Although an element of exclusion is probably inevitable, the extent to which it occurs varies across organizations. This suggests that both exclusion and its consequences can be alleviated. An applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
303
0
21

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(341 citation statements)
references
References 32 publications
17
303
0
21
Order By: Relevance
“…In large, continuously innovating firms, the strategic apex sets strategic direction, but innovation occurs at the front lines, on the shop floor, or in small designated teams. Top management does not so much ''control or direct'' the innovation process, as provide resources and opportunities for exploration and experimentation (Nonaka and Nishiguchi 2001;Westley 1990). There is a key role here for intermediaries, or knowledge brokers, at the middle management level, who are able to question the strategic context to understand why and where a firm wishes to move, frame that for those working on the front lines, identify promising innovations, and sell these to the strategic apex (Nonaka and Takeuchi 1995;Burgelman 1983).…”
Section: Tipping Toward Sustainability: Understanding and Supporting mentioning
confidence: 99%
“…In large, continuously innovating firms, the strategic apex sets strategic direction, but innovation occurs at the front lines, on the shop floor, or in small designated teams. Top management does not so much ''control or direct'' the innovation process, as provide resources and opportunities for exploration and experimentation (Nonaka and Nishiguchi 2001;Westley 1990). There is a key role here for intermediaries, or knowledge brokers, at the middle management level, who are able to question the strategic context to understand why and where a firm wishes to move, frame that for those working on the front lines, identify promising innovations, and sell these to the strategic apex (Nonaka and Takeuchi 1995;Burgelman 1983).…”
Section: Tipping Toward Sustainability: Understanding and Supporting mentioning
confidence: 99%
“…Scholars have shown that MM who experience role conflict can suffer from ''reluctance'' (Goffee and Scase 1992), ''disillusionment'' and ''disaffection'' (Johnson and Frohman 1989), or ''paralysis'' (Westley 1990). Indeed, Dess et al (2003) argue that managers caught in role conflict are unlikely to display entrepreneurial behavior successfully, which will disrupt the information exchange needed for CE.…”
Section: Role Conflict and Exploratory Innovationmentioning
confidence: 99%
“…A third, and the most related body of work to our research, explores the cognitive processes of middle managers' involvement in strategy (e.g., Balogun and Johnson, 2004;Dutton et al, 1997;Guth and MacMillan, 1986;Huy et al, 2014;Mangaliso, 1995;Ren and Guo, 2011;Westley, 1990). For example, Balogun and Johnson's (2004), and Rouleau and Balogun's (2011) studies reveal the pivotal role of middle managers in sense-making during organisational change.…”
Section: The Strategic Role Of Middle Managersmentioning
confidence: 99%
“…This sentiment is echoed in numerous studies indicating that participation in strategic decision-making is likely to increase knowledge and commitment to strategic decisions and improve execution (e.g., Raes et al, 2011;Raman, 2009;Suominen and Mantere, 2010;Westley, 1990;Floyd, 1989, 1990). It is a concept that also appears in strategic involvement, commitment and goal setting research (e.g., Lawler, 1999;Locke and Latham, 1990).…”
Section: Individual Antecedents Of Strategy Knowledgementioning
confidence: 99%
See 1 more Smart Citation